Transformation of Binjai City Spatial Planning Information Through Development and Maintenance WebGIS Based Web (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Digital transformation in spatial planning management is an important requirement for local governments in providing information Which accurate, latest, And easy accessible. City Binjai as region urban The ever-evolving spatial information system requires a spatial information system capable of effectively integrating spatial and non-spatial data. This study aims to realize the transformation of spatial information in Binjai City through the development and maintenance of web-based WebGIS. The research methods used include inventory and identification of geospatial data availability, processing and updating spatial data, and designing and implementing a WebGIS system. The data used consist of the Indonesian Topographic Map (RBI) at a scale of 1:10,000–1:25,000, high-resolution satellite imagery of Spot 7, base maps, thematic maps, and spatial planning maps. WebGIS development is carried out using open source technology, namely PostgreSQL/PostGIS as a spatial database, GeoServer as a geospatial data server, and LeafletJS as a web-based mapping interface. The research results show that the developed WebGIS is capable of presenting spatial information about Binjai City interactively and in an integrated manner, including base maps, thematic maps, and spatial planning maps. Furthermore, the system maintenance strategy involves regular data updates and database management. support sustainability and reliability WebGIS. Existence WebGIS This contribute to improvement accessibility, transparency, and effectiveness provision information order room, as well as support spatial data-based decision making.